Analisa Persepsi Mahasiswa Akuntansi Terhadap Tanggung Jawab Auditor "(Studi Komparasi Antar Perguruan Tinggi di Kota Bengkulu)" - Yusnita, Yuli; Riandita, Nansi (Jurnal Adminitrasi Bisnis Nusantara, 2025)
The research has conducted examination to perception of accounting student toward auditor's responsibility according to the student's opinion. The analysis based on collected data of 60 respondents of the research from questioners by purposive sampling method based on the opinions. The questioners have spread directly to applicants both in and outside the class. Data analyzing method used Independent T-test Sample to tested the difference perception of accounting students in non-private university (UNIB) and private university (UMB and UNIVE D) who took Auditing I lectures and they who has and had take Auditing II lectures. The result bas shown that there are differences perceptions of accounting students in both non-private and private university about the auditor's responsibility.